Influence of Perceptual-Motor Calibration on the Perception of Geographical Slope. (June 2020) - Linkenauger, Sally A.; Rose Readman, Megan
Individuals drastically overestimate geographic slant. Research has suggested this occurs as the amount of energy it would take to ascend the slope modulates the perceived steepness. Numerous studies have provided evidence that alterations in current physiological potential can influence perceptions of geographical slant. However, it is unclear whether these influences are solely due to one's actual physiological state or whether anticipation of energy expenditure also influences perceived slope. To investigate this, we manipulated anticipated energy expenditure while maintaining actual physiological state by altering the coupling between optic flow and gait. Using virtual reality, we calibrated individuals to either large changes (low anticipated expenditure) or small changes (large anticipated expenditure) in optic flow when walking at the same speed. Following optic flow calibration, individuals estimated slopes of various degrees. The results obtained provide evidence that perceptions of geographical slant are influenced by anticipated energy expenditure.